Industrial-Based Learning (IBL): Promoting Excellent on Polytechnics and Vocational Higher Education - Ilyas, Ismet P.; Semiawan, Transimissia (UI Scholars Hub, 2017)
The industrial sector plays an important role in the national and global economy. A significant global change has shaped many industries recently: That is, industrial operation modes have shifted from local to global markets. Digital business and the implementation of extended enterprise are becoming a new playground and have become strategies for survival. Based on this, we find that more practical and business-oriented education (polytechnics and vocational higher education (PVHE), specifically) is actively participating and playing an important role in industrializing the nation. The current and future competitiveness of national industry depends on highly educated and motivated professionals, as their capabilities are critical to future industry viability. and vocational higher education (PVHE) in Indonesia are required to be included as major drivers with important roles in promoting excellence for national industry, leveraging their competitive advantages, and leveling up the national economics in order to cope with global challenges in the years to come[1]. In general, the practice of most PVHE in Indonesia has been carried out separately and independently from industry. It is difficult for industry to comprehend and adapt directly to the technological advances from the PVHE. Therefore, PVHE needs a new collaboration approach in order to prepare industry for innovation and to maintain its competitive advantages. This paper will discuss a specific implementation of manufacturing education in one PVHE in Indonesia, known as Politeknik Manufaktur (POLMAN) Bandung. The discussion emphasizes the way in which POLMAN Bandung carries out manufacturing education by means of an Industrial-Based Learning (IBL) model that embraces collaboration between education and industry. Implemented in the last two decades, POLMAN Bandung’s IBL model has shown its quality as a promising breakthrough for integrating a “real” industry environment with the education concept. With IBL, POLMAN Bandung has been able to establish a new definition and education paradigms within which direct involvement of all stakeholders is carried out through a number of collaborative actions linking needs of both the industrial and education systems. Moreover, IBL brings up a number of important issues in manufacturing education, such as embedding entrepreneurship and innovation within the education system, providing an education model as a means of developing qualified workforces and professionals for new job environments, and promoting an integrated approach of Tri-Dharma Perguruan Tinggi (education and training, research and technology transfers, and community services). POLMAN Bandung IBL is one of promising models in manufacturing education as it is able to address a number of emerging challenges related to industry, academia and society in general (including government); as well as to comprehend the implementation of knowledge transfer to maintain technological excellence in industry. Furthermore, POLMAN Bandung IBL also promotes and develops competency and professionalism that can be used as a strategic framework for promoting productive teaching and active learning at the PVHE in general.